Cody and the fountain of happiness - Springstubb, Tricia (Candlewick Press, 2015)
A girl named Cody is looking forward to a great summer vacation, but dealing with her mopey older brother, busy mother, and a father away on a long distance truck delivery don't promise a good start, until she meets a new friend in search of a lost cat.